Biology and development of xanthopimpla pedator (hymenoptera: ichneumonidae): pupal endoparasitoid of antheraea mylitta (Lepidoptera: Saturniidae) - Gathalkar, Ganesh B.; Barsagade, Deepak D.; Sen, Avalokiteswar (Annals of the Entomological Society of America, 2017)
The Antheraea mylitta (Drury) (Lepidoptera: Saturniidae) is a commercially important species for the production of tasar silk. However, the Xanthopimpla pedator (F.) (Hymenoptera: Ichneumonidae) is a major pupal endoparasitoid of A. mylitta, which affects the total tasar silk production in India. A gravid female X. pedator parasitizes the pupae of A. mylitta by depositing an egg, which produces a single offspring per host. We studied the development of immature forms of X. pedator by dissecting parasitized pupae of A. mylitta under laboratory conditions at 28-30 degrees C and 40-60% relative humidity. All immature stages of the parasitoid develop within the host in 20-22 d, by devouring the entire pupal content, resulting in dead or seedless cocoons. The total life cycle of X. pedator is completed inside the host pupa and the adult emerges out by rupturing the peduncle end of the cocoon. During development of X. pedator, five preimaginal stages, viz., egg, larval instars, prepupa, pupa, and a pharate adult, were observed. Xanthopimpla pedator passes through five larval instars identified by structural and morphometric variations. These include primary larva (L1), the intermediate larvae (L2-L4), and the finalinstar larva (L5). Biometric study and larval head width permitted the morphological separation of all five larval instars. In the present study, the biology and development of X. pedator inside the pupa of A. mylitta are reported for the first time with detailed photomicrographs. Therefore, the study may enable the information concerning physiological interactions between A. mylitta and its endoparasitoid, X. pedator.

Blends of neem oil based polyesteramide as nanofiber mats to control Culicidae - Konchada, Sravanya; Killi, Naresh; Sayyad, Shahebaz; Gathalkar, Ganesh B.; Gundloori, Rathna V. N. (RSC Advances, 2020)
Mosquitoes act as vectors for several disease-causing microorganisms and pose a threat to mankind by transmitting various diseases. There are different conventional methods to repel or kill these mosquitoes for avoiding susceptibility against infections. However, to overcome the difficulties with conventional methods, new advanced materials are being studied. For the first time, we report developing a nanofiber mat with a controlled release of insecticide to repel or detain the mosquitoes. Briefly, various blend compositions were prepared by manipulating the ratio of neem oil-based polyesteramide (PEA) and polycaprolactone (PCL) immobilized with insecticide, transfluthrin (Tf). The blend solutions were electrospun to get non-woven nanofiber mats, and these nanomaterials were characterized by various spectroscopic techniques to understand their physicochemical properties. The surface morphology was analyzed using environmental scanning electron microscopy (E-SEM), and the diameter of the nanofibers was in the range of 200 to 450 nm. Further, thermal and mechanical properties were evaluated to understand the stability of nanofiber mats. In vitro drug release studies of nanofiber mat PPT-1335 showed controlled and sustained release of Tf, with similar to 35% of Tf released in 24 h. However, a film of the same composition (PPT-1335) showed similar to 5% of Tf release within 24 h. Moreover, in vivo bio-efficacy studies suggested the mortality of mosquitoes was about 50% with PP-133, which was further increased to 100% within 12 h in the presence of Tf (PPT-1335). However, 60% mortality of mosquitoes was observed with the film of PPT-1335. Hence, the nanofiber mat showed better efficacy against mosquitoes as compared to the film of the same composition. The degradation studies under various conditions revealed biocompatibility of the developed nanofiber mats with the ecosystem.

Identification of a novel series of potent organosilicon mosquito repellents - Kulkarni, Akshay S.; Ramesh, Remya; Walia, Safal; Sayyad, Shahebaz I.; Gathalkar, Ganesh B.; Balamkundu, Seetharamsing; Joshi, Manali; Sen, Avalokiteswar; Reddy, D. Srinivasa (ACS Omega, 2021)
Mosquito control by personal protection is one of the most efficient ways of curtailing deadly diseases such as malaria and dengue with the potential to save millions of lives per year. DEET (N,N-diethyl-3-methyl benzamide) is currently considered as the gold standard for mosquito repellents, being used for the past several decades. Control by DEET, however, is being threatened by emerging resistance among mosquitoes. To address this concern and also to improve protection times, we synthesized a novel series of 25 silicon-containing acyl piperidines using acid–amine coupling protocol and tested their activity against Aedes aegypti in mosquito-repellent assays. Several compounds from this series appear to possess good mosquito-repellent properties. Most notably, at 0.5 mg/cm2 concentrations, the mean protection time for NDS100100 was 756 min, which was higher than that of DEET (616 min). The details of design, synthesis, and biological evaluation are discussed herein.

New record of larval-pupal endoparasitoid Exorista deligata parasitising Indian Tea looper Hyposidra talaca from India - Sharma, Pooja V.; Das, Tamal; Mukherjee, Susmita; Pathan, Ejaj K.; Rahman, Azizur; Gathalkar, Ganesh B. (Phytoparasitica, 2024)
This is the first record of Exorista deligata (Pandell & eacute;, 1896) (Diptera: Tachinidae) as a parasitoid of Hyposidra talaca (Walker, 1860) (Lepidoptera: Geometridae) from India. H. talaca is a major and new emerging defoliator of the Tea plant Camellia sinensis (L) Kuntze (Theaceae). It completes multiple generations per year without diapause on C. sinensis, resulting in heavy crop loss. The field-collected larvae/pupa of H. talaca were checked for parasitoid infestations and reared until either the host or parasitoid emerged. The parasitoid was identified as E. deligata with morphological characteristics and confirmed by the mitochondrial cytochrome oxidase subunit-I (COX-CO1) gene sequencing technique. The parasitoid is infrequent with unexplored parasitic biology. It parasitises the larva and completes its lifecycle inside the developing H. talaca by entirely devouring the host. The mean percent parasitisation caused by E. deligata studied herein was 25.4% (range 5.88%-57.69%). Based on its parasitisation ability, we suggest the species could be a potential biological control agent to address the damage mitigation caused by the tea looper pest, H. talaca.
Keywords: Biocontrol; Exorista deligata; Hyposidra talaca; Invasive pest; Parasitisation

Endophytic entomopathogenic fungi: the next frontier in mycological biocontrol - Patil, Karan S.; Gathalkar, Ganesh B.; Pathan, Ejaj K. (World Journal of Microbiology & Biotechnology, 2026)
Entomopathogenic fungi (EPF) are eco-friendly alternatives to chemical pesticides. However, high costs, the instability of the formulations, sensitivity to environmental factors and variability in virulence limit adoption by farmers. We argue that these problems can be overcome by using EPF strains established as endophytes. The ability of endophytic entomopathogenic fungi (EEPF) to modulate the release of volatiles to attract the predators of insect pests positions them as dual-purpose biocontrol agents in agriculture. As endophytes, these fungi are persistent, lowering the costs for pest control. Endophytic entomopathogenic fungi can also promote plant growth and improve tolerance to abiotic stress. Research on the molecular mechanisms underlying plant tissue colonization by EEPF, their persistence in plants and virulence towards insects suggests that EEPF acquire virulence factors and metabolic versatility through horizontal gene transfer from plants. Therefore, establishing and maintaining EPF as endophytes within plants may compensate for the loss of virulence associated with repeated in vitro subculturing of EPF on artificial media. However, despite these potential advantages of EEPF, challenges still remain, such as variability in endophytic colonization under field conditions, host specificity, ecological risks, and scalability. This review critically evaluates these limitations, focusing on well-studied genera, such as Metarhizium, Beauveria, and Lecanicillium, and outlines future directions for improving the reliability of the application of EEPF. By integrating ecological, molecular, and applied perspectives, we provide a comprehensive and updated framework that positions EEPF as next-generation biocontrol agents in sustainable agriculture.Graphical AbstractEndophytic entomopathogenic fungi protect plants by infecting insect pests and emitting volatiles to attract the natural predators of insect pests. They also promote plant growth by improving the nitrogen fixation and nutrient cycling
Keywords: Beauveria; Metarhizium; Biological control; Endophytic fungi; Entomopathogens; horizontal gene transfer; Plant-fungus interactions; Sustainable agriculture

Morphological characteristics of antennal microstructure and its ecological significance in xanthopimpla pedator (hymenoptera: ichneumonidae: pimplinae): insights into cocoon-concealed host detection - Gathalkar, Ganesh B.; Sharma, V. Pooja; Barsagade, Deepak D. (Microscopy and Microanalysis, 2026)
Xanthopimpla pedator (Fabricius) (Hymenoptera: Ichneumonidae: Pimplinae) is a specialist solitary pupal endoparasitoid of the tropical Tasar silkworm, Antheraea mylitta (Drury) (Lepidoptera: Saturniidae), causing significant ecological and economic losses each year. Female oviposits into cocoon-concealed pupae of A. mylitta, where the developing larva consumes the host, ultimately killing it. During host searching, females rely on their antennae as the principal sensory organs to detect and evaluate host suitability, although sensory structures on the ovipositor may also contribute to oviposition decisions. Scanning electron microscopy (SEM) revealed nine distinct microstructure/sensilla types: trichodea, basiconica, chaetica, placodea, grooved peg sensilla, campaniformia, microtrichia, B & ouml;hm's bristles, and glandular pores, including their respective subtypes. Additional microstructures, such as apical pegs, cuticular pores, and cuticular folds, were also observed. Sensilla trichodea were most abundant, followed by placodea, chaetica, and basiconica. Apical pegs at the antennal apex in both sexes are hypothesized to function in vibrational sounding during antennal tapping. Minimal sexual dimorphism in antennal sensilla was observed, limited to antennal length and flagellomere counts. These antennal features, including chemosensory and mechanosensory sensilla, are likely essential for host detection, discrimination, and oviposition, providing insights that could inform the development of semiochemical-based pest management tactics.
Keywords: antennal sensilla; endoparasitoid; host detection; scanning electron microscopy; tasar silkworm; ultrastructure